STRATEGI KOMUNIKASI DALAM DISKUSI KELOMPOK: SEBUAH KAJIAN PADA MAHASISWA JURUSAN PENDIDIKAN BAHASA INGGRIS - Rosmania Rima (Fakultas Komunikasi, Sastra, dan Bahasa, 2016)
This study investigated the types and reasons for employing communication strategies in group discussion at the third year students of English Department of FKIP Sultan Ageng Tirtayasa University joining psycholinguistics subject. It was descriptive qualitative research, observing the types and reasons of communication strategies. Field notes, video recording, and interview guide were used as the instruments to collect the data. The findings of the study show that the students employed twelve Dornyei's Classification of Communication Strategy (1995). The reasons for employing communication strategies employed are: to avoid talking about topic the subjects are not familiar with; to avoid being trap in some linguistic difficulties; to express the idea quickly and more easily; to spontaneously response to the flow of discussion; to emphasis what is expressed orally; to ask for incomprehensible vocabulary items and to confirm idea as well; to express the intended meaning; to fill in the gap while the speaker gains time thinking about what to say next; and to support the speech effectively when one strategy seems not to work well in overcoming the communication problem.